An Exaggerated Monocyte-Derived Cytokine Response to Candida Hyphae in Patients With Recurrent Vulvovaginal Candidiasis. (23rd July 2020) - Rosati, Diletta; Bruno, Mariolina; Jaeger, Martin; Kullberg, Bart-Jan; van de Veerdonk, Frank; Netea, Mihai G; ten Oever, Jaap
Abstract: Background: Recurrent vulvovaginal candidiasis (RVVC) affects up to 8% of women. The immunopathogenesis is poorly understood but it has been suggested that RVVC might be due to dysregulated innate immune response. The aim of this study was to compare cytokine profiles in stimulated primary mononuclear cells (PBMCs) from RVVC and healthy individuals. Methods: PBMCs isolated from RVVC patients (n = 24) and healthy volunteers (n = 30) were stimulated with unspecific and pathogen-specific antigens. Cytokine production was assessed after 24 hours, 48 hours, and 7 days using ELISA. Results: No significant differences in cytokine production were found in T helper 1 (Th1), Th2, and Th17 immunity in response to both unspecific and pathogen-specific stimulations. Tumor necrosis factor-α (TNF-α) production in response to C. albicans hyphae was significantly higher in patients than controls and within the patient group, a significant positive correlation was found between interleukin-1β (IL-1β) and both TNF-α and IL-6. Both IL-1β/IL-1Ra and TNF-α/IL-10 ratios in Candida hyphae-stimulated PBMCs were significantly higher in patients than controls. Conclusions: Women affected by RVVC showed increased monocytes-derived cytokine production, which might contribute to an exaggerated vaginal immune response to Candida hyphae. RVVC patients show no defective Th-dependent adaptive immune response upon Candida stimulation. Abstract : Peripheral blood mononuclear cell stimulations show an increased monocytes-derived cytokine production, but a normal T helper cell function, in women with recurrent vulvovaginal candidiasis (RVVC). This suggest autoinflammation rather than immunodeficiency to be central in the pathogenesis of RVVC.